Intolerance of uncertainty and negative metacognitive beliefs as transdiagnostic mediators of repetitive negative thinking in a clinical sample with anxiety disorders - McEvoy, Peter; Mahoney, A. (Pergamon, 2013)
This study aimed to replicate and extend a hierarchical model of vulnerability to worry, with neuroticism and extraversion as higher-order factors and negative metacognitions and intolerance of uncertainty as second-order factors. The model also included a transdiagnostic measure of repetitive negative thinking (RNT) and depression symptoms as outcome variables to determine whether relationships would extend beyond worry, which has traditionally been studied within the context of generalized anxiety disorder (GAD). Participants (N = 99) were referrals to a specialist anxiety disorders clinic with a principal anxiety disorder who completed a battery of self-report questionnaires assessing neuroticism, extraversion, metacognitions, intolerance of uncertainty, worry, RNT, and depression symptoms. Mediational analyses using bootstrapping provided support for transdiagnostic and diagnosis-specific mediation effects. Negative metacognitions fully mediated the relationship between neuroticism and RNT for the whole sample and for subsamples with and without GAD. Intolerance of uncertainty mediated the relationship between neuroticism and worry (for the whole sample and for those with GAD) and between neuroticism and RNT (for those with GAD). Implications for theory, treatment, and nosology are discussed.